A Study of Effect of Knowledge, Attitude, And Practice on The Diabetic Patient with Counselling as Intervention - A Non-Randomized Community-Based Trial from Gujarat - Manoj Kumar; Niraj Pandit (Medsci Publications, 2022)
Introduction: Lifestyle modification is key to management of diabetes. Behavioural change is key to adopt lifestyle modification. The current study was planned with objective to assess the impact of counselling on knowledge, attitude, and practices among patients with diabetes mellitus in rural and urban areas of Gujarat. Method: It was a non-randomized interventional study conducted in the state of Gujarat, India. Known cases of diabetes were enrolled for the study. Two equal size groups of study participants from urban and rural area were divided equally for intervention group (N=77; 28 urban +49 Rural) and control group (N=77; 28 urban +49 Rural). Regular counselling on role of diet in DM management, self-care, deaddiction, role of physical activity, and drug compliance was given by community physician for three months to 6 months. Pre and post intervention KAP score was collected and evaluated. Result: The knowledge, attitude and practice score were increased among counselling group in comparison to traditional treatment group in both urban and rural area. The score increased from 5.4 to 10.4 in knowledge; 3.07 to 5.07 in attitude and 5.07 to 8.92 in practice among urban participants. Similarly, the score increased from 4.14 to 7.16 in knowledge, 2.57 to 3.67 in attitude and 4.73 to 7.42 in practice among rural participants. Conclusion: With counselling the knowledge, practice and attitude of chronic patients are improving. The study recommended that counselling services should be available to all diabetes patients. It should be available to patients at their doorstep if possible as study depict.